Treating Obesity in Latino Children: A Systematic Review of Current Interventions - Leung, May May; Cavalcanti, Olivia Barata; Dada, Amani El; Brown, Mason; Mateo, Katrina F.; Yeh, Ming Chin (International Journal of Child Health and Nutrition, 2017)
Childhood obesity remains a significant public health issue in the U.S. and globally. Rates are disproportionately higher in Latinos than other ethnic groups. This review provides a qualitative synthesis of the current evidence for childhood obesity treatment interventions among Latino children. A systematic search was performed in PubMed, Web of Science and Google Scholar for articles published from September 2010 to December 2015. Randomized controlled trials treating childhood overweight/obesity in Latino children ages 5-19 focused on diet and/or physical activity (PA) behaviors were included. Of the records initially identified (n=1,592), 11 studies met the inclusionary criteria. The majority included a family-based component (n=8; 73%). Nearly half (n=5) focused on children ages 5-12, with three specifically developed for the pre-adolescence stage (ages 8-12). Nine studies acknowledged cultural tailoring, most frequently by seeking input from their intended population and utilizing bilingual delivery staff. Improvements in anthropometric measures (e.g. body mass index (BMI) z-score) were observed in 55% of the studies (n=6). Many interventions with a combined focus of diet and PA, in the form of nutrition education in a group setting and in-person activity/exercise sessions and incorporated a parent/family component reported positive anthropometric results. Three (27%) studies included a follow-up period, all of which observed a sustained decrease in BMI over time. Overall, family-based interventions focusing on both diet and PA demonstrated promising results. However, additional research incorporating a follow-up period is warranted to assess sustainability of these outcomes. Additionally, more interventions could be developed specifically for the critical developmental stage of pre-adolescence